Proposals for Development Programme for the Year 1970-71 Part I Descriptive Chapters Government of Gujarat - Planning Commission (Planning Commission, 1970)
Along with the development of minor irrigation, considerable emphasis is also laid on increasing the irrigation facilities through major and medium irrigation schemes. All the spillover major and medium irrigation schemes including Kakrapar and Mahi State I are proposed to be completed in the the Fourth Plan. It 'is also planned to complete the work of Unit I (Dam) and Unit II (Power) of the Ukai Project during the Fourth Plan. The works on the canals will also be completed partially. Irrigation potential created through multipurpose, major and medium irrigation schemes is likely to increase from 4.35 lakh hectares at the end of 1968-69 to 8.39 lakh hectares by the end of the Fourth Plan while corresponding utilisation is expected to increase from 3.08 lakh hectares to 6.32 lakh hectares.
Government of Gujarat, General Administration Department